Failure of thick rubber vulcanizates by blowout / Che Mohamad Som Said - Said, Che Mohamad Som (Institute of Graduate Studies, UiTM, 2014)
tyres is associated with temperature rise known as blowout that occurs in the thick shoulder regions of the tyre. It occurs due to various dissipative processes under dynamic deformations. The heat produced is sufficiently high to cause thermal degradation that produces volatiles, which consequently exerts internal pressure sufficiently large to tear open a path to the exterior. Blowout failure may cause fatal road accidents. Although the tyre industry is aware of the problem, research in this area is still inadequate apart from the work conducted by Gent and Hindi in 1988, Choi and Kim in 1998 and Park in 2000. The factors affecting heat generation are still not fully investigated, thus the work presented in this thesis has covered the areas which are not covered by the previous researchers. This includes the work to investigate the effects of glass-transition temperature, Tg of the rubber, partcicle size of the filler, structure of filler, viscosity of process oil and coupling agent on silicafilled vulcanizate on temperature rise and blowout failure.